Antiscalants used in the desalination industry impact the physiology of the coral Montipora capricornis. (1st February 2023) - Marques, Joseane A; Gafni, Almog; Adler, Osher; Levy, Oren; Bar-Zeev, Edo
Highlights: Antiscalants (ASs) have a clear effect on the physiology of M. capricornis coral. Polyphosphonate-based AS led to coral bleaching after two weeks of exposure. Polyphosphonate-based AS enhanced algal chlorophyll a and oxidative stress. Bacterial numbers increased after exposure to polymer and polyphosphonate-based AS. Abstract: Many coral reefs are found in arid and semi-arid regions that often face severe water scarcity and depend on seawater desalination for freshwater supply. Alongside freshwater production, desalination plants discharge brine waste into the sea. Brine includes various chemicals (e.g., antiscalants) that may harm the coastal environment. Although widely used, little is known about the ecotoxicological effects of antiscalants (AS) on hard corals. This study compared the impacts of polyphosphonate-based and polymer-based ASs on the coral Montipora capricornis . After two weeks of exposure, we determined the effects of AS on coral physiology, symbiotic microalgae, and associated bacteria, using various analytical approaches such as optical coherence tomography, pulse amplitude modulated fluorometry, and oxidative stress biomarkers. Both ASs reduced polyp activity (∼25%) and caused tissue damage (30% and 41% for polymer and polyphosphonate based AS, respectively). In addition, exposure to polyphosphonate-based AS decreased the abundance of endosymbiotic algae (39%) and upregulated the antioxidant capacity of the animal host (45%). The microalgal symbionts were under oxidative stress, with increased levels of antioxidant capacity and oxidative damage (a 2-fold increase compared to the control). Interestingly, exposure to AS enhanced the numbers of associated bacteria (∼40% compared to the control seawater) regardless of the AS type. Our results introduce new insights into the effects of brine on the physiology of hard corals, highlighting that choosing AS type must be examined according to the receiving ecosystem. Graphical abstract: Image, graphical abstract .